Development of Cooperative Learning Model Modeling The Way in Drama Playing Learning for Class VIII Junior High School Students - Hidayat Nur Septiadi; Agnes Apryliana; Sabrina Cahya Eri (Universitas Sebelas Maret, 2022)
This study aims to develop a cooperative learning model, Modeling the Way, for teaching drama to eighth-grade junior high school students. The model is designed to enhance students' drama performance skills while instilling character values such as teamwork, creativity, and responsibility. The research employs the Research and Development (R&D) approach by adapting Borg & Gall's steps, including preliminary studies, planning, initial product development, trials, evaluations, and finalizing the model. The results show that the Modeling the Way model is effective in improving student engagement, drama performance skills, and character development. Through observation, modeling, and group collaboration, students could better understand drama techniques while demonstrating improvements in communication, collaboration, and self-expression. Thus, this model can be implemented as an alternative approach to arts and culture education in junior high schools.